Students' Perceptions of Geography Teacher Learning Strategies in Distance Education - Pahleviannur, Muhammad Rizal (Indonesian Journal Publisher, 2024)
This study aims to determine students' perception of geography teacher learning strategy during the COVID-19 pandemic at SMA Negeri 1 Wonosari Klaten. This study uses a quantitative type with a correlation research design. This study showed that in the facilitator indicators, according to students, geography teachers provide facilities and ease in the teaching and learning process. The highest percentage agrees with 44% and creates an atmosphere of practical learning activities. The highest percentage agree with 31%. According to students’ geography, teachers carry out learning activities on the information indicator, the highest percentage agrees with 37%, and the source of information on academic activities for students, the highest percentage agrees with 37%. According to students with geography teachers manage academic activities on the organiser indicator, the highest percentage agree at 19%, and the syllabus with the highest percentage of lesson schedule agree at 39%. On the mediator indicator, according to students’ geography, teachers lead student discussion activities with the highest percentage at 35%, and the arbiter in student discussion activities with the highest percentage at 36%. On motivator indicators, according to students' geography, teachers boost students' potential with the highest percentage agreeing at 39% and increase student creativity with 46%. On the initiator indicator, according to the geography teacher, students are the originators of creative ideas in the learning process, and the highest percentage agreed with 38% and had the initiative of using online learning media; the highest percentage agreed with 38%. On the transmitter indicator, according to students' geography, teachers act as the highest percentage of education policy spreaders who agree with 35% and provide knowledgeable information to students. The highest percentage agree at 38%. In evaluator indicators, according to students' geography, teachers rate students in academic fields with the highest percentage at 33% and rate social behaviour as a determinant of student achievement success in learning activities with the highest percentage at 36%. Given the importance of online learning strategies, teachers are expected to develop learning strategies through educational technology.